The Improvisation Between Method and Attitude:Didactic Potential for Education Today and Tomorrow (Itinera, 2015)
This essay wants to reflect upon the concept and practice of improvisation, showing how improvisation could be an educational possible perspective to allow to schools and teachers to fulfill educational requests of contemporary society. Starting from theoretical and social considerations, the essay faces what means to improvise in teaching, when it is possible for a teacher to improvise while he/she is teaching, and why this practice could be generative for an authentic human development.